CASH WAQF LINKED DEPOSITS: MAQASHID AL-SYARIAH PERSPECTIVE - Nur Arbaien, Muhamad Fasya; Nurkaromah, Silvia Ripa (LPPM IAIT, 2025)
Cash Waqf Linked deposits can be a sustainable investment instrument proposed by Islam to help maintain the ratio of public expenditure by, for, and of the people without involving interest rates. It is hoped that with the legalization of CWLD, the distribution of benefits of cash waqf will be more comprehensive and based on justice, not just limited to certain parties. CWLD contracts, on the other hand, need to be reviewed for their alignment with the public good from the Maqashid al-Syariah perspective. This research uses a descriptive method with a qualitative approach. The data analysis was conducted using three main steps: data reduction, data display, and data verification. The result of this research confirms that the CWLD scheme is in accordance with Maqashid Al-Syariah. The objectives of Muhafaẓah al-Din, Muhafaẓah al-Nafs, Muhafaẓah al-'Aql, Muhafazah al-Maal, and Muhafazah al-Nasl are interconnected in the CWLD scheme offered. However, in implementation, it is necessary to have specific monitoring from the sharia committee to maintain the consistency of its sharia compliance.